Bosnia and Herzegovina’s Surprising Export Performance : Back to the Past in a New Veil but Will It Last? - Kaminski, Bartlomiej; Ng, Francis (2012)
Bosnia and Herzegovina's industrial restructuring, as seen through the lenses of foreign trade performance and its sustainability, has taken off. Bosnia and Herzegovina s exports have displayed strong dynamics outstripping the pace of growth of exports in almost each year over 1997-2007 combined with the shift to higher value added exportables. Although its performance during the period 1996-2000 following the end of war in late 1995 was not surprising, given relatively low foreign direct investment inflows and weaknesses in the investment climate, its subsequent export performance has come as a surprise. Industrial restructuring, as revealed in the pattern of exports, consisted in rebuilding and modernizing the pre-independence industrial base built around wood products, metalworking, clothing, and automotive products. Although exports still remain relatively low in terms of both per capita and gross domestic product in comparison with other Balkan economies, there has been significant change in their composition, indicating a growing presence of more processed manufactures and the participation of local firms in global networks of production and distribution, mostly as independent suppliers. Firms with foreign participation have been one of the levers of export upgrading and expansion. The dominance of joint ventures as a mode of entry of foreign capital is worrisome for two reasons: first, domestic firms may not have access to the most recent technologies and knowhow; and second, it is always indicative of weaknesses of a domestic economic regime. This also raises concerns about the future sustainability of export performance.